ANALISIS PELAKSANAAN PEMBELAJARAN JARAK JAUH BERBASIS E-LEARNING PADA MASA PANDEMI COVID-19 MAHASISWA DI JURUSAN PENDIDIKAN IPS FKIP UNIVERSITAS RIAU - Indra Primahardani; Dedi Futra; Riki Apriyandi Putra (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2021)
This study aims to describe and analyze about: forms of e-learning-based distance learning activities carried out at the Department of Social Studies FKIP Riau. This type of research is descriptive qualitative research. The data to be collected is ordinal data, which comes from the results of e-questionnaires(google form). The data collected is summative response scale,using a modified Likert scale with 3 answer options. Student responses are organized based on 3 levels of Likert Scale: 1 = Yes; 2 = No; 3 = Hesitation. The data obtained is then analyzed through a descriptive statistical analysis of percentages. The results showed that the form of implementation of distance learning activities carried out in the department of Social Sciences FKIP Riau University refers to the indicators of distance learning, namely: clear learning objectives, relevant to the needs, quality of education, efficient and effectiveness of the program, equality and expansion of learning opportunities, independence, integration and sustainability.